Agreement between two cephalometric analyses of facial growth direction and biotype = Concordancia entre dos análisis cefalométricos de dirección de crecimiento y biotipo facial - Aguilar Pérez, Fernando Javier; Bataller Mendez, Eugenia Beatriz; Colome Ruiz, Gabriel Eduardo; Chuc Gamboa, Martha Gabriela; Aguilar Perez, David Alejandro (2024)
Cephalometry is a morphological and descriptive diagnostic method that provides relevant data on skeletal and dentoalveolar malocclusions of patients seeking orthodontics treatment. Several authors have proposed different cephalometric measurements to determine facial growth direction and facial biotype, the results of these different measurements from the same patient do not always agree on the diagnosis. The aim of this study was to determine the level of agreement between Ricketts and Björk-Jarabak cephalometric analyses for the determination of facial growth direction and facial biotype in patients from a population of Yucatan, Mexico. A total of 260 lateral cephalograms of patients between 18 and 59 years of age were digitally traced using the Ricketts and Björk-Jarabak cephalometric analyses to determine the direction of facial growth and facial biotype using Dolphin Imagine software. Cohen's kappa statistical test was performed to establish the strength of agreement between the diagnostic results obtained by the cephalometric analyses. A poor diagnostic concordance strength was found for growth direction (K=0.105), and acceptable for facial biotype (K=0.362). The concordance strengths for each diagnostic possibility (level) ranged from slight to acceptable, except for the brachyfacial and dolichofacial biotypes, with a moderate strength of agreement. In conclusion, the Ricketts and Björk-Jarabak cephalometric measurements used for the determination of facial biotype and facial growth direction could suggest non-concordant diagnostic assessments in some individuals.
La cefalometría es un método diagnóstico morfológico y descriptivo que proporciona datos relevantes sobre maloclusiones esqueléticas y dentoalveolares de pacientes que buscan tratamiento de ortodoncia. Varios autores han propuesto diferentes mediciones cefalométricas para determinar la dirección del crecimiento facial y el biotipo facial, los resultados de estas diferentes mediciones de un mismo paciente no siempre coinciden en el diagnóstico. El objetivo de este estudio fue determinar el nivel de concordancia entre los análisis cefalométricos de Ricketts y Björk-Jarabak para la determinación de la dirección del crecimiento facial y el biotipo facial en pacientes de una población de Yucatán, México. Se trazaron digitalmente un total de 260 cefalogramas laterales de pacientes entre 18 y 59 años de edad utilizando los análisis cefalométricos de Ricketts y Björk-Jarabak para determinar la dirección del crecimiento facial y el biotipo facial utilizando el software Dolphin Imagine. Se realizó la prueba estadística kappa de Cohen para establecer la fuerza de concordancia entre los resultados diagnósticos obtenidos por los análisis cefalométricos. Se encontró una fuerza de concordancia diagnóstica deficiente para la dirección del crecimiento (K=0.105) y aceptable para el biotipo facial (K=0.362). Los niveles de concordancia para cada posibilidad diagnóstica (nivel) variaron de leve a aceptable, excepto para los biotipos braquifacial y dolicofacial, con un nivel de concordancia moderado. En conclusión, las mediciones cefalométricas de Ricketts y Björk-Jarabak utilizadas para la determinación del biotipo facial y la dirección del crecimiento facial podrían sugerir evaluaciones diagnósticas no concordantes en algunos individuos.
En revista Odóvtos, vol. 26, no.2 (mayo-agosto 2024)
Descripción basada en el contenido visto el 04 de febrero, 2025
También disponible en formato HTML y EPUB